Show me Thai. - Amornpichetkul, Chittima; Poshyananda, Apinan (Tokyo : Museum of Contemporary Art Tokyo, 2007)
Apichatkriengkral, Wijit ; Apisuk, Chumpon ; Boonma, Montien ; Boonyavanishkul, Rearngsak ; Buabusaya, Jitr ; Buasan, Deang ; Buddhacharoen, Phatyos ; Charernsuphkul, Kanya ; Chowtadapong, Somsak ; Dachanee, Thawan ; Emcharoen, Pratuang ; Endo, Ryuta ; Ikeda Ichi ; Kasornsuwan, Tinnakorn ; Ko-Udomvit, Thavorn ; Kobayashi, Keisei ; Kongwaree, Amnat ; Kunavichayanont, Sutee ; Kunchaethong, Yanawit ; Kurachi, Hisashi ; Kurae, Napapon ; Kusolwong Surasi ; Lertchaiprasert, Kamin ; Methapisit, Suwan ; Milindasuta, Sansern ; Morimura, Yasumasa ; Mukdamanee, Vichoke ; Nakiraks, Chalerm ; Nara, Yoshimoto ; Nimsamer, Chalood ; Nirand, Pichai ; Nobuyoshi, Araki ; Oranniwesna, Nipan ; Osathanugrah, Surat ; Phaosavasdi, Kamol ; Ponnimit, Wisut ; Pratchayaratikun, Sittichai ; Puipia, Chatchai ; Puntusawasdi, Tawatchai ; Rasdjarmrearnsook, Araya ; Rawanchaikul, Navin ; Rimsakul, Porntaweesak ; Sanpitak, Pinaree ; Satsara, Supachai ; Sitthiket, Vasan ; SOI Project ; Srisukprasert, Thongchai ; Srisuta, Praphan ; Srithongdee, Thaweesak ; Sriwanichpoom, Manit ; Suwankusolsong, Natthapol ; Takahama, Toshiya ; Tangcharoen, Pichit ; Tantisuk, Parinya ; Tantisuk, Sawasdi ; Thaothong, Preecha ; Thiensoonthorn, Sermsuk ; Tiravanija, Rirkrit ; Toemsombat, Montri ; Uluchadha, Prayura ; Vijinthanasarn, Panya ; Vilasineekul, Jakapan ; Weerasethakul, Apichatpong ; Wong-Uparaj, Damrong ; Yamaguchi, Hirokazu ; Yimsiri, Khien ; Yipintsoi, Misiem ; Yokota, Niro ; Yukantapornpong, Thongchai
biog. p. 161-170
Engels
Japans
Show me Thai. Museum of Contemporary Art Tokyo. 2007-04-18. 2007-05-20
boek
Keywords: Japan; Thailand